Journal of Health, Population and Nutrition - Baqui, Abdullah; Cousens, Simon
Journal of Health, Population and Nutrition brings together research on all aspects of issues related to population, nutrition and health. The journal publishes articles across a broad range of topics including global health, maternal and child health, nutrition, common illnesses and determinants of population health. The journal considers all aspects of global health, and includes but is not limited to, the following sections: ·         Non-communicable diseases ·         Respiratory diseases ·         Gastrointestinal diseases ·         Vector-Borne diseases ·         Zoonotic diseases ·         Sexually transmitted diseases ·         Health economics ·         Health systems ·         Under-nutrition ·         Over-nutrition ·         Reproductive health and family planning ·         Maternal, new born and child health.